Epigallocatechin gallate reverses cTnI‐low expression‐induced age‐related heart diastolic dysfunction through histone acetylation modification. Issue 10 (6th April 2017) - Pan, Bo; Quan, Junjun; Liu, Lingjuan; Xu, Zhongwei; Zhu, Jing; Huang, Xupei; Tian, Jie
Abstract: Cardiac diastolic dysfunction (CDD) is the most common form of cardiovascular disorders, especially in elderly people. Cardiac troponin I (cTnI) plays a critical role in the regulation of cardiac function, especially diastolic function. Our previous studies showed that cTnI‐low expression induced by histone acetylation modification might be one of the causes that result in diastolic dysfunction in ageing hearts. This study was designed to investigate whether epigallocatechin‐3‐gallate (EGCG) would modify histone acetylation events to regulate cTnI expression and then improve cardiac functions in ageing mice. Our study shows that EGCG improved cardiac diastolic function of aged mice after 8‐week treatment. Low expression of cTnI in the ageing hearts was reversed through EGCG treatment. EGCG inhibited the expression of histone deacetylase 1 (HDAC1) and HDAC3, and the binding levels of HDAC1 in the proximal promoter of cTnI. Acetylated lysine 9 on histone H3 (AcH3K9) levels of cTnI's promoter were increased through EGCG treatment. Additionally, EGCG resulted in an ascent of the binding levels of transcription factors GATA4 and Mef2c with cTnI's promoter. Together, our data indicate that EGCG may improve cardiac diastolic function of ageing mice through up‐regulating cTnI by histone acetylation modification. These findings provide new insights into histone acetylation mechanisms of EGCG treatment that may contribute to the prevention of CDD in ageing populations.